Dampak Ekonomi Hijau Terhadap Pertumbuhan Ekonomi - Bonaraja Purba; Bethlehem Efrata Sitanggang; Lola Vitaloka; Novianti Naibaho; Selfiana Lumban Batu (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The aim of this research is to evaluate the impact of the green economy on economic growth. This research used a systematic, clear, and repeatable literature review methodology. This data comes from research published in scientific journals over the last ten years. As the analysis shows, the green economy has a significant positive effect on economic growth. Efficient use of resources and reduced energy costs increase economic resilience and business competitiveness and reduce the costs of environmental damage. Overall, the green economy promotes sustainable economic growth by reducing operational costs, increasing public awareness, encouraging technological innovation, strengthening supportive policies, and increasing capacity and access to natural resources.